Regulation of CCR7-dependent cell migration through CCR7 homodimer formation - Kobayashi D; Endo M; Ochi H; Hojo H; Miyasaka M; Hayasaka H (NATURE PUBLISHING GROUP, 2022)
The chemokine receptor CCR7 contributes to various physiological and pathological processes including T cell maturation, T cell migration from the blood into secondary lymphoid tissues, and tumor cell metastasis to lymph nodes. Although a previous study suggested that the efficacy of CCR7 ligand-dependent T cell migration correlates with CCR7 homo- and heterodimer formation, the exact extent of contribution of the CCR7 dimerization remains unclear. Here, by inducing or disrupting CCR7 dimers, we demonstrated a direct contribution of CCR7 homodimerization to CCR7-dependent cell migration and signaling. Induction of stable CCR7 homodimerization resulted in enhanced CCR7-dependent cell migration and CCL19 binding, whereas induction of CXCR4/CCR7 heterodimerization did not. In contrast, dissociation of CCR7 homodimerization by a novel CCR7-derived synthetic peptide attenuated CCR7-dependent cell migration, ligand-dependent CCR7 internalization, ligand-induced actin rearrangement, and Akt and Erk signaling in CCR7-expressing cells. Our study indicates that CCR7 homodimerization critically regulates CCR7 ligand- dependent cell migration and intracellular signaling in multiple cell types.